Combined reconstructive surgery involving uterosacral colpopexy and anterior vaginal mesh implantation for pelvic organ prolapse. Issue 6 (24th February 2016) - Hamuro, A.; Tachibana, D.; Wang, H.; Hayashi, M.; Yanai, S.; Kurihara, Y.; Misugi, T.; Katayama, H.; Nakano, A.; Koyama, M.
Abstract: Aim: The optimal treatment for pelvic organ prolapse has been the subject of much discussion. The aim of this study was to assess the utility of a combination of uterosacral colpopexy and anterior vaginal mesh implantation. Methods: A single‐center prospective cohort study was conducted. Twenty‐eight patients with stage III–IV cystocele and uterine prolapse underwent reconstructive surgery. A combination of vaginal hysterectomy, McCall culdeplasty, and trocar‐guided anterior vaginal mesh implantation was performed, and the patients' postoperative outcomes were analyzed. Patient satisfaction was investigated using the modified Short Form 12 version 2 (SF‐12v2) questionnaire, and interviews regarding sexual behavior were conducted at 1 postoperative year. Results: A bladder injury occurred during the dissection in one case (3.6%). Recurrent vaginal vault prolapse beyond the hymen was observed in one patient (cure rate: 96.4%), and further mesh augmentation was required in this case. Another patient developed mild cystocele (Ba = 0), but was simply observed because she did not complain of any symptoms caused by vaginal descent. We did not experience any other mesh‐related complications, such as protrusion, chronic pain, or chronic inflammation, during the follow‐up period. The patients' modified SF‐12 scores at 12 months were significantly better than their preoperative scores in all eight domains. Conclusion: The satisfactory correction of pelvic organ prolapse was achieved using a combination of vaginal hysterectomy and uterosacral ligament colpopexy augmented by anterior vaginal mesh implantation. © 2016 Japan Society of Obstetrics and Gynecology